Geomorphology of the upper Kalguty Basin, Ukok Plateau, Russian Altai mountains. Issue 2 (9th December 2020) - Deline, Philip; Ravanel, Ludovic; Delannoy, Jean-Jacques; Le Roy, Melaine; Molodin, Vyacheslav I.; Cheremisim, Dimitri V.; Zotkina, Lydia V.; Cretin, Catherine; Geneste, Jean-Michel; Plisson, Hugues
ABSTRACT: As part of an archaeological research project, we investigate the geomorphology of the cold and arid study area by combining field mapping with use of orthoimages and DEM. To the north of a broad trunk valley floor, gentle slopes continuously vegetated culminate around 3000 m, while to the south steep slopes reaching to 3500 m are deeply incised and covered mainly by regolith. The basin has been intensively glaciated as evidenced by the till covering the gentler slopes, several morainic complexes, kame terraces and roches moutonnées. The present morphodynamics of this permafrost-affected basin is mainly periglacial, with blockfields, solifluction lobes, patterned ground and rock glaciers on gentle slopes to high-elevated flat terrain, and block slopes and rockfall talus on steeper slopes. Large alluvial fans at the outlet of the steep lateral valleys constrain the anastomosing channel of the Kalguty river. Active braided channels in those valleys evidence seasonal high peak discharge.